Alternative Splicing in Neurogenesis and Brain Development - Su, Chun-Hao; D, Dhananjaya; Tarn, Woan-Yuh (Frontiers in Molecular Biosciences, 2018)
Alternative splicing of precursor mRNA is an important mechanism that increases transcriptomic and proteomic diversity and also post-transcriptionally regulates mRNA levels. Alternative splicing occurs at high frequency in brain tissues and contributes to every step of nervous system development, including cell-fate decisions, neuronal migration, axon guidance, and synaptogenesis. Genetic manipulation and RNA sequencing have provided insights into the molecular mechanisms underlying the effects of alternative splicing in stem cell self-renewal and neuronal fate specification. Timely expression and perhaps post-translational modification of neuron-specific splicing regulators play important roles in neuronal development. Alternative splicing of many key transcription regulators or epigenetic factors reprograms the transcriptome and hence contributes to stem cell fate determination. During neuronal differentiation, alternative splicing also modulates signaling activity, centriolar dynamics, and metabolic pathways. Moreover, alternative splicing impacts cortical lamination and neuronal development and function. In this review, we focus on recent progress towards understanding the contributions of alternative splicing to neurogenesis and brain development, which has shed light on how splicing defects may cause brain disorders and diseases.